EVALUASI KECEPATAN TRANSAKSI DI GERBANG TOL PASTEUR BANDUNG - Ramayanti, Lisa; Santosa, Wimpy (Jurnal Transportasi, 2009)
Bandung, the capital of the West Java Province, is one of the big cities in Indonesia. To meet high demands for movement, the Purbaleunyi toll road was built in this area. One of the toll gates in this toll road is Pasteur toll gate, which functions as the main entrance for the city of Bandung. Very often traffic congestion or long queue occurs in this toll gate, particularly during peak hours. This study aims to evaluate the toll road service performance, specifically the transaction speed at the entrance and exit gates located in the Pasteur toll gate. According to the Toll Road Minimum Service Standard, the time of transaction at the entrance gates should be no more than 7 seconds per vehicle and at the exit gates it should not exceed 11 seconds per vehicle. This study found that at the entrance gate, only 92.93% and 90.78% of transactions meet the Toll Road Minimum Service Standard for peak hours and normal hours, respectively. Meanwhile, at the exit gate, only 81.93% and 71.49% of transactions during peak hours and normal hours, respectively, meet the Toll Road Minimum Service Standard.Keywords: toll gate, transaction speed, toll roads minimum service standard